2017
DOI: 10.1111/eve.12785
|View full text |Cite
|
Sign up to set email alerts
|

Splenic abscessation in the horse: A retrospective study of 12 cases

Abstract: Summary This paper summarises the clinical findings of 12 cases of splenic abscessation in horses presented to Texas A&M University Veterinary Medical Teaching Hospital from 1993 to 2015. The objective of this study was to describe the signalment, clinical and laboratory findings, diagnostics, treatment and outcome of horses affected with splenic abscessation. Only horses in which a splenic abscess was confirmed by microbiological or cytological confirmation from a percutaneous, surgical, or necropsy sample we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 15 publications
(33 reference statements)
3
29
0
Order By: Relevance
“…Secondary abscesses may be caused by ulceration, perforation, or trauma to the gastrointestinal tract (Rumbaugh et al . 1978; Coleman and Schmitz 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Secondary abscesses may be caused by ulceration, perforation, or trauma to the gastrointestinal tract (Rumbaugh et al . 1978; Coleman and Schmitz 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases of splenic abscesses where an exploratory laparotomy has been performed have been euthanised during surgery due to abdominal adhesions, and the need for aggressive surgical manipulation with a poor prognosis (Rosso et al . 2012; Coleman and Schmitz 2019). A retrospective study reported clinical and laboratory findings in 12 horses with splenic abscessation; none of these horses survived to discharge (Coleman and Schmitz 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations